PENGARUH KEPEMIMPINAN PERUBAHAN KEPALA SEKOLAH, PEMBELAJARAN MENDALAM, DAN IKLIM SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA KELAS XI SMA DI NAWARIPI TIMIKA - Mentauli Hutabarat; C. Tanta; Diki Kurniawan; Monika Gultom; Kusdianto Kusdianto; Albaiti Albaiti (STKIP Pesisir Selatan, 2026)
This study aims to examine the partial and simultaneous effects of change leadership, deep learning, and school climate on senior high school students’ learning motivation in Papua Tengah. This research employed a quantitative associative approach with a correlational design. The population consisted of Grade XI students from three senior high schools in Nawaripi Timika, Papua Tengah. A total of 254 respondents were selected using simple random sampling. Data were collected through validated Likert-scale questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 22. The findings reveal that change leadership has a positive and significant effect on students’ learning motivation. Deep learning has a highly significant effect and emerges as the most dominant predictor. School climate does not show a significant partial effect. However, simultaneously, change leadership, deep learning, and school climate have a significant effect on students’ learning motivation. This study offers an integrated empirical model that combines change leadership, deep learning, and school climate within a single analytical framework in the context of Papua Tengah, an underrepresented region in educational research, thereby contributing to the development of educational management literature in geographically diverse settings.